A genealogia acadêmica da ciência da informação brasileira: análise dos currículos dos pesquisadores/docentes - Carlos Alexandre de Oliveira (2021)
The Brazilian Science is developed in academic laboratories of existing graduate programs mainly, at federal universities. There, new researchers (masters and doctors) are graduated and absorbed by the country’s scientific system itself. In such process, one must highlight the performance of researchers that advise the masters and doctors to-be. They contribute to the scientific progress, producing new scientific knowledge to the society and educating new generations of researchers. The objective of the research is identifying and characterizing the professors/researchers linked to the Information Science Graduate Programs (ISGPs). To achieve it, resumes hosted at the Lattes Platform are analyzed. One hundred fifty-five (155) professors/researchers linked to the ISGPs – which hold academic courses of master’s and doctor’s degrees, and with records of academic advising at the doctorate level – are selected. For the data analyses, the following categories are considered: academic profile, fecundity, fertility, descendancy, generation, and academic ancestry. The results reveal that the group of 155 researchers performs a total of 2.785 academic advising in ISGPs. There are 1.974 master´s dissertations and 811 doctoral theses. In the academic profile, the data show that the majority of researchers are women (56,77%). They are aged between 50 and 59 (36,77%), and are linked to institutions of the southeast region (63,23%). In the doctorate, the degree was obtained between the years of 2000 and 2009 (50,32%), at the University of São Paulo (22,58%) in an Information Science Program (41,94%). The analyses by Google Analytics find that Lena Vania Ribeiro Pinheiro (IBICT) is the researcher with the highest academic productivity in the field. Also, Professor Maria Nélida González de Gomez (IBICT) is highlighted as having the highest rates to fertility, descendancy and academic generation. Among all institutions, the Federal University of Minas Gerais stands out with the highest rates of fecundity, descendancy and academic generation. IBICT registers the highest rate of academic fertility. The academic ancestors total 193 identified ascendant researchers. Out of these, 14 researchers stand out for the capacity of generating academic descendants, which are active in the education of researchers for the Brazilian Information Science. Currently, 25 ascendant researchers hold active linkages to the ISGPs. It is observed that the academic provenance of the investigated researchers/professors is fragmented, having 82 distinct academic ancestors as an origin core. It concludes that the academic advising activity, within the graduate programs, constitutes a central stage for the scientific development of the Information Science in Brazil; the researchers/professors GA analysis enables the acknowledgement of those that contribute the most with the education of new researchers to the Information Science and, consequently, to the education of the scientific community in Brazil.